2007
DOI: 10.1074/jbc.m611871200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of β-Catenin by AKT Promotes β-Catenin Transcriptional Activity

Abstract: Increased transcriptional activity of ␤-catenin resulting from Wnt/Wingless-dependent or -independent signaling has been detected in many types of human cancer, but the underlying mechanism of Wnt-independent regulation is poorly understood. We have demonstrated that AKT, which is activated downstream from epidermal growth factor receptor signaling, phosphorylates ␤-catenin at Ser 552 in vitro and in vivo. AKTmediated phosphorylation of ␤-catenin causes its disassociation from cell-cell contacts and accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
715
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 774 publications
(789 citation statements)
references
References 70 publications
56
715
7
Order By: Relevance
“…Rac1 was included, as it functions upstream of PAK1. Forskolin, a potent activator of PKA, was used as a positive control (Hino et al, 2005;Fang et al, 2007). As expected, both S552 and S675 were heavily phosphorylated upon forskolin treatment (Figure 3b).…”
Section: Pak1 Is Required For Proliferation Of Colon Cancer Cellssupporting
confidence: 61%
See 1 more Smart Citation
“…Rac1 was included, as it functions upstream of PAK1. Forskolin, a potent activator of PKA, was used as a positive control (Hino et al, 2005;Fang et al, 2007). As expected, both S552 and S675 were heavily phosphorylated upon forskolin treatment (Figure 3b).…”
Section: Pak1 Is Required For Proliferation Of Colon Cancer Cellssupporting
confidence: 61%
“…The key event of both Wnt signaling transduction and cancerous cell proliferation is the regulation of b-catenin stability and activity. In addition to its N-terminal residues, Ser552 (Fang et al, 2007) and Ser675 (Hino et al, 2005;Taurin et al, 2006) of b-catenin have also been identified as potential phosphorylation sites and may affect its signaling activity or protein stability.…”
Section: Introductionmentioning
confidence: 99%
“…AKT can phosphorylate β-catenin at the Ser 552 residue resulting in its activation and nuclear translocation from the cytosol. 11 Kinetic analysis in infected macrophages with phospho-β-catenin Ser552 antibodies showed increasing phosphorylation of β-catenin with a maximum of 3.0-fold over control at 6 h post infection (Figure 4a). This increased phosphorylation coincided with its nuclear localization (Figure 4b), thus indicating the role of AKT in β-catenin activation.…”
Section: Resultsmentioning
confidence: 98%
“…33 Phosphorylation of β-catenin by AKT at Ser 552 residue has been shown to enhance its transcriptional activity. 11 Upon AKT inhibition in L. donovani infection a decrease in nuclear translocation of β-catenin was observed indicating a role of AKT-mediated β-catenin regulation. β-catenin is known to be degraded upon phosphorylation by GSK-3β at the Ser 33/37 but no phosphorylation was observed at the Ser 33/37 in MG132 treated infected cells further validating that GSK-3β gets inactivated in infection as a result of which it fails to inactivate β-catenin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation